Identifikasi Nilai Erodibilitas Tanah Menggunakan Platform Google Earth Engine (GEE) di DAS Limboto Provinsi Gorontalo - Ahmadong, Ainun Jaria; Maryati, Sri; Lahay, Rakhmat Jaya (Universitas Negeri Gorontalo, 2024)
Limboto watershed is one of the watersheds in Gorontalo Province that is categorised as critical priority. This condition is caused by land degradation in the catchment area (DTA) due to uncontrolled land conversion in the upstream part of the river. The purpose of this research is to determine the soil erodibility value based on soil texture in Limboto watershed. The erodibility value in this study was obtained by matching the soil texture of the Limboto watershed from the USDA soil texture image with the soil erodibility table from Hamza (2017). The results showed that soil erodibility values in the Limboto watershed varied according to soil texture, with sandy clay loam having the lowest erodibility value (0.0264), clay (0.288), and clay loam the highest (0.394). Most areas of the watershed, especially those with high erodibility, require conservation measures to reduce erosion risk. This approach is expected to provide practical solutions in sustainable land management.